Study on the correlation between the concentration of plasma lipoprotein-associated phospholipase A2 and coronary heart disease - Jin-Ming Cen (KeAi Communications Co., Ltd., 2015)
Objective: This study explores the correlation between plasma lipoprotein-associated phospholipase A2 (Lp-PLA2) and coronary heart disease (CHD) by comparing the level of plasma Lp-PLA2 in the plasma of patients with different types of CHD. Methods: Blood samples were collected from 56 patients diagnosed with CHD by the Department of Cardiology of the First People's Hospital of Foshan and 34 healthy subjects from February 2013 to January 2014. We measured the concentration of plasma Lp-PLA2 and determined the levels of total cholesterol (Tch), triglyceride (TG), apolipoprotein A1 (Apo-A1), apolipoprotein B (Apo-B), high density lipoprotein-cholesterol (HDL-c), low density lipoprotein-cholesterol (LDL-c), lipoprotein a (Lp(a)), glucose (Glu), and high-sensitivity C-reactive protein (hs-CRP). The concentration of plasma Lp-PLA2 in the healthy control group and each subgroup of CHD patients were compared and analyzed for correlations of plasma Lp-PLA2 between the patients in different CHD subgroups and several laboratory indicators. Results: The concentration of plasma Lp-PLA2 in each subgroup of CHD was significantly higher than in the control group (P < 0.05). The concentration of Lp-PLA2 in the unstable angina pectoris (UAP) group and acute myocardial infarction (AMI) group were significantly higher than in the stable angina pectoris (SAP) group (P < 0.05), and the concentration of plasma Lp-PLA2 in the AMI group was significantly higher than in the UAP group (P < 0.05). The concentration of plasma Lp-PLA2 in the CHD group merely showed a positive correlation (r = 0.493, P < 0.05) with the hs-CRP group, but the levels of Tch, TG, Apo-A1, Apo-B, HDL-c, LDL-c, Lp(a) and Glu did not. Conclusions: The concentration of plasma Lp-PLA2 in patients with CHD was higher than that in the control group. The concentration of plasma Lp-PLA2 in the subgroups of CHD patients varied greatly from each other. The inflammatory response of atherosclerosis might be resulted from the synergy of plasma Lp-PLA2 and hs-CRP. Keywords: Coronary heart disease, Plasma lipoprotein-associated phospholipase A2, Atherosclerosis